2002
DOI: 10.1038/sj.gt.3301671
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of microvessels in vivo upon dimerization of iCaspase-9

Abstract: Anti-angiogenic therapies based on targeted disruption of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 34 publications
0
45
1
1
Order By: Relevance
“…This was somewhat lower than we expected initially, because we had observed before that approximately 90% of the endothelial cells stably expressing iCaspase-9 undergo apoptosis upon exposure to AP20187, 9 and that about 90% of the endothelial cells were positive for b-gal when AdhVEGFR2-LacZ was used here. These puzzling findings were perhaps clarified when we performed immunostaining in endothelial cells infected with Ad-hVEGFR2-iCaspase-9 and observed that only about 48% of the cells actually expressed iCaspase-9.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…This was somewhat lower than we expected initially, because we had observed before that approximately 90% of the endothelial cells stably expressing iCaspase-9 undergo apoptosis upon exposure to AP20187, 9 and that about 90% of the endothelial cells were positive for b-gal when AdhVEGFR2-LacZ was used here. These puzzling findings were perhaps clarified when we performed immunostaining in endothelial cells infected with Ad-hVEGFR2-iCaspase-9 and observed that only about 48% of the cells actually expressed iCaspase-9.…”
Section: Discussioncontrasting
confidence: 52%
“…[5][6][7][8] We have recently demonstrated that the direct activation of caspase-9 induces apoptosis of proliferating endothelial cells, that the endothelial cell survival factors VEGF and bFGF do not protect these cells against apoptosis, and that activated iCaspase-9 is sufficient to disrupt blood vessels in vivo. 9 These experiments established proof-of-principle data to support the concept that direct activation of a proapoptotic caspase in endothelial cells might be beneficial for the treatment of solid tumors. 9 However, the utilization of a caspase-based artificial death switch as an antiangiogenic therapeutic strategy would require that the therapeutic gene be expressed only in neovascular endothelial cells, and not expressed in mature blood vessels.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations